2021
DOI: 10.26855/ijfsa.2021.03.022
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Medicinal Plant Piper cubeba L. and Its Pharmaceutical Properties

Abstract: Plants are regarded as the richest research for many potential drugs. Medicinal plants have been used for the treatment of various diseases since ancient time. The bioactive compounds like different phytochemicals are extracted from various parts of the medicinal plants, as they serve as traditional herbal drugs. These drugs are well recognized in modern medication system due to natural products, much safer, effective in curing various diseases and it have less side effects. The secondary metabolite like tanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It isbeing cultivated worldwide and grows in dry warm climates. This plant is grown commercially in United States and Chile, as well as in Arabia, Persia, China, India, and Japan ( Kumar, 2021 ). It has a religious importance in Muslims and Christanity ( Slavin, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…It isbeing cultivated worldwide and grows in dry warm climates. This plant is grown commercially in United States and Chile, as well as in Arabia, Persia, China, India, and Japan ( Kumar, 2021 ). It has a religious importance in Muslims and Christanity ( Slavin, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…Berries, leaves, and stalks are widely exploited in spice market, and also used as food preservative, coloring aid and in cosmetics (9)(10)(11).…”
Section: Compound Name Referencesmentioning
confidence: 99%
“…These include antioxidant, anti-cancer, anti-inflammatory, anti-diabetic, antiparasitic, antibacterial activities in addition to its ability to modulate melanogenesis ( 6 9 ). Furthermore, a recent study revealed promising hepato- and renoprotective activities by the plant ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%